Using Constraint Programming to Manage Configurations in Self-Adaptive Systems. - Sawyer, Pete; Mazo, Raúl; Diaz, Daniel; Salinesi, Camille; Hughes, Danny (Computer (00189162), 2012)
Combining goal-modeling techniques with constraint programming provides the means to identify the variants best suited to the environmental contexts that a self-adaptive software system might encounter at runtime. The Web extra at http://youtu.be/q-oheenSq2E is a slide show demonstrating the deployment of GridStix sensor nodes in wireless sensor network to provide flood warning on the rivers Ribble and Dee in England and Wales, respectively.